INFLUENCE OF LAND SUBSIDENCE AND CORROSION DEFECT ON THE X52 PIPELINE USING FINITE ELEMENT METHOD - Jeremy Ishak, Elkan
Pipelines are one of the most important methods of fluid transportation in the oil and gas industry. In practice, the pipes can be buried in the ground or above ground. Buried pipes bear a heavier load than those laid on the ground. One of the most common cases is land subsidence. In this study, simulations were carried out using the finite element method to evaluate whether the pipe will fail under land subsidence condition, calculating the maximum land subsidence before the pipe failed, analyzing the factors and parameters that affect pipe reliability, and analyzing the effect of corrosion defects to pipe reliability. Simulations were carried out on two API 5L X52 PSL 2 pipes, each of which has a diameter of 8 inches and 16 inches, and both are 0.5 inches thick. Both pipes experienced land subsidence with a maximum subsidence of 2 meters. Experiments to measure the maximum land subsidence were also carried out. Variations in the D/t ratio in pipe 1 were also carried out with values of 8, 16, 20, 25, and 32 at internal pressures of 3.1 Mpa, 4 Mpa, 5.2 Mpa, and 8 Mpa. To determine the effect of corrosion defects, the pipe assumed having a localized thinning area with oval geometry and the final thickness was 7.67 mm. Variations in the location of corrosion defects are carried out on the inner side of the pipe and outer side of the pipe. Variations in the size of the corrosion defects were carried out by changing the length of the oval to 100 mm, 200 mm, 400 mm, and 600 mm with the width kept constant at 50 mm. The opposite experiment was also carried out by variating the oval width to 50 mm, 100 mm, 150 mm, and 175 mm with the length being kept constant at 50 mm. Results indicate that the 8 inch diameter pipe is still within the safe limit, while the 16 inch diameter pipe exceeds the safe limit, but yielding has not occurred yet. The maximum land subsidence of pipe 1 with internal pressure of 3.1 Mpa is 8.55 meters. The ratio D/t and internal pressure affect the equivalent von Mises stress. The greater the value of the ratio of D/t and internal pressure, the value of the equivalent von Mises stress also increases. In addition, the effect of corrosion defects on the inner side of the pipe will cause a much higher potential for failure than the corrosion defects that occur on the outer side of the pipe. The larger the dimensions of corrosion in the direction of pipe length and depth of corrosion defects, the equivalent von Mises stress will increase. The size of the corrosion dimension in the radial direction does not affect the equivalent von Mises stress as long as the size is not close to the pipe diameter.